Translation research and interpreting research : traditions, gaps and synergies - Schäffner, Christina (Current Issues in Language and Society Monographs, 2004)
Despite differences, translation and interpreting have much in common. This volume focuses on aspects of conducting research into these two modes. It reviews recent developments and explores kinship, differences and prospects for partnership between translation research and interpreting research.